Stability results for backward time-fractional parabolic equations. (19th November 2019) - Nho Hào, Dinh; Liu, Jijun; Van Duc, Nguyen; Van Thang, Nguyen
Abstract: Optimal order stability estimates of Hölder type for the backward Caputo time-fractional abstract parabolic equations are obtained. This ill-posed problem is regularized by a non-local boundary value problem method with a priori and a posteriori parameter choice rules which guarantee error estimates of Hölder type. Numerical implementations are presented to show the validity of the proposed scheme.